Komodifikasi Hijab: Pergeseran Makna Jilbab Antara Identitas Religius dan Tren Fashion di Kalangan Mahasiswa Pekanbaru - Annisa Rahma Luthfi; Dhea Reza Nirmala; Winda Permata Astuti; Sukma Erni (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
The veil is a form of civilization that was known hundreds of years before the arrival of Islam. The veil as a head covering is only known in Indonesia. Initially worn by teenage girls to reject traditional clothing (kebaya). In Islam, Allah commands every Muslim woman to cover her private parts by holding out her veil. Psychologically, the veil is a symbol of a set of values ​​that soothe the soul. It turns out that the hijab phenomenon is understood differently by students. Some of them are of the opinion that what is widely worn is not the hijab but the headscarf which only covers the private parts. The use of headscarves among students is not only a step towards following existing rules on campus but also because of an obligation as Muslims. However, wearing a headscarf is said to be more practical in Indonesia. Innovation in the hijab is not only in terms of material, shape and method or style of wearing it, but also many students wear the hijab currently, namely the Paris hijab and there are also those who wear long hijabs up to the knees with various kinds of basic materials. There are several forms of headscarves used by students, namely; rectangular veil that has a square shape. Likewise with the model or style of wearing it, such as having one side of the hijab pinned to the shoulder and the other one let fall down. The findings of this research illustrate that today's headscarf styles are not only a matter of religion but are also cultural because headscarves have been created so that the styles of wearing them are increasingly diverse. Wearing a headscarf is a step towards appearance or style in clothing.